Creating strategic fit: Aligning servant leadership with organizational structure and strategy. Issue 1 (5th February 2018) - Eva, Nathan; Sendjaya, Sen; Prajogo, Daniel; Cavanagh, Andrew; Robin, Mulyadi
Abstract : Purpose: While research and adoption of servant leadership are on the increase, little is known about the mechanisms through which it affects organizational performance. Drawing on the contingency theory, the purpose of this paper is to examine the extent to which organizational strategy and structure affect the relationship between servant leadership and organizational performance. Design/methodology/approach: Survey data were collected from 336 direct reports of CEOs/GM/MDs in Australian SMEs, and multiple regression analysis was used in the hypotheses testing. Findings: The study found that the relationship between servant leadership and performance is moderated by the three-way interaction effects of differentiation and centralization as well as cost leadership and formalization. Practical implications: This study shows that the positive effects of servant leadership on performance are more pronounced in organizations with minimal organizational structure that are not fixated on cost minimization. To that end, ensuring that there is a fit among organizational strategy, structure, and leadership is a key priority for senior executives. Originality/value: This research is one of the first to examine the boundary conditions of servant leadership, demonstrating the effects organizational structure has on servant leadership's influence. Further, this research extends the contingency theory by focusing on strategy and structure, rather than just structural impacts.